2013
DOI: 10.1002/emmm.201302655
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for decorin in bladder cancer invasiveness

Abstract: Muscle-invasive forms of urothelial carcinomas are responsible for most mortality in bladder cancer. Finding new treatments for invasive bladder tumours requires adequate animal models to decipher the mechanisms of progression, in particular the way tumours interact with their microenvironment. Herein, using the murine bladder tumour cell line MB49 and its more aggressive variant MB49-I, we demonstrate that the adaptive immune system efficiently limits progression of MB49, whereas MB49-I has lost tumour antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 59 publications
0
32
1
Order By: Relevance
“…Leygue et al 39 had shown in breast cancer and Suhovskih et al 40 in prostatic cancer that the mRNA expression of Decorin was significantly lower in tumour tissue compared with normal tissue. On the contrary to the report published by El Behi et al 41 that states overexpression of Decorin in muscle invasive bladder cancer, we observed a reduced protein expression of Decorin by IHC and western blotting in tumour tissue as compared with adjacent non-tumour tissue. Previously, Sainio et al 42 had shown a similar low stromal Decorin expression in areas rich in bladder cancer cells as compared with non-malignant bladder tissue, and Oda et al 43 had observed a reduced immunostaining in stroma of invasive cancer and in situ breast cancer as compared with normal breast tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…Leygue et al 39 had shown in breast cancer and Suhovskih et al 40 in prostatic cancer that the mRNA expression of Decorin was significantly lower in tumour tissue compared with normal tissue. On the contrary to the report published by El Behi et al 41 that states overexpression of Decorin in muscle invasive bladder cancer, we observed a reduced protein expression of Decorin by IHC and western blotting in tumour tissue as compared with adjacent non-tumour tissue. Previously, Sainio et al 42 had shown a similar low stromal Decorin expression in areas rich in bladder cancer cells as compared with non-malignant bladder tissue, and Oda et al 43 had observed a reduced immunostaining in stroma of invasive cancer and in situ breast cancer as compared with normal breast tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…Transcriptomic data obtained with Affymetrix U133plus2.0 DNA arrays for our CIT‐cohorts of bladder tumors, encompassing 82 NMIBCs and 85 MIBCs, were previously deposited on the publicly available ArrayExpress databases E‐MTAB‐1803 and E‐MTAB‐1940, respectively (El Behi et al , ; Biton et al , ; Rebouissou et al , ). RNA‐Seq data for an independent cohort of 416 tumors were available from ArrayExpress E‐MTAB‐4321 (Hedegaard et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Various mRNAs encoding collagen chain components were either up‐ ( COL8A1 , COL12A1 and COL28A1 ) or down‐regulated ( COL17A1 ). Of note, over‐expression of decorin , fibronectin 1 and collagen chains COL8A1 and COL12A1 has recently been shown to promote invasiveness of various cancer types. These results indicate that c‐Src(mt) significantly alters cell–matrix interactions, thereby decreasing cell adhesion and promoting cellular migration and invasiveness.…”
Section: Resultsmentioning
confidence: 99%